Telling a Story from Watching a Movie Potentially Improving Students’ Oral Communication - Lia Agustina (Journal of ELT, Linguistics, and Literature, 2015)
Watching a movie in a class has not always been really appreciated by administrators in education since they considered it as something used by teachers when teachers do not have anything better to do. But watching a movie in an appropriate way can be really useful for students since: a). students would learn English in a natural way and associating vocabulary to a context,   as presenting vocabulary within a context is important. b). movies are a tool for communication; it is motivated than just doing exercises in students notebooks, c). students are motivated to express ideas and therefore they would feel important as being involve in class, d). moviesoffer a visual context  aids,     besides verbal language, there is also color, movement, and sound, the class would be livelier. Movie-viewing experiences and it also creates more student-teacher and student-student discussions.